Khảo sát tính cách sinh viên kỹ thuật thông qua DISC profile hỗ trợ công tác cố vấn học tập - Châu, Võ Trần Thị Bích; Linh, Đoàn Thị Trúc (Tạp chí Khoa học Đại học Cần Thơ, 2016)
DISC Profile (Dominance – Influence – Steadiness - Conscientiousness) is called the thorough person’s skill, become an effective tool for everyone to identify his or her personality, as well as the associate should revise for having good at communication habits of highlight. However, the model has been applied in some large companies but has not been used in Vietnamese universities. This research presents a survey of 237 students in the field of Industrial Management such as 65 students of freshmen, 92 students of sophomores, 40 students of juniors, and 40 students of seniors. The purpose of this research aims to determine the students’ personality so that academic consultants can provide their students with a better orientation strategy such as promoting their strengths, being the professional direction from the beginning. DISC Profile (Dominance – Influence - Steadiness - Conscientiousness) - Thuật thấu hiểu lòng người là công cụ để mỗi người tự nhận diện tính cách của mình cũng như đối phương, từ đó có cách giao tiếp phù hợp nhất. Mặc dù, mô hình đã được áp dụng tại một số công ty lớn, nhưng chưa được áp dụng trong môi trường đại học tại Việt Nam. Bài viết trình bày kết quả khảo sát 237 sinh viên các năm như 65 sinh viên năm nhất (K41), 92 sinh viên năm hai (K40), 40 sinh viên năm ba (K39), 40 sinh viên năm cuối (K38) của ngành Quản lý Công nghiệp. Mục đích của nghiên cứu là xác định tính cách sinh viên từ đó giúp cố vấn học tập định hướng giáo dục sinh viên tốt hơn như định hướng cách phát huy tính cách nổi trội của họ, định hướng nghề nghiệp từ ban đầu.